A Comprehensive Review on Amplification of Laser Pulses via Stimulated Raman Scattering and Stimulated Brillouin Scattering in Plasmas - Renju Miriam Cheriyan; Nikhil Varghese; R. S. Sooraj; Kavya H. Rao; N. Smijesh (Plasma, 2022)
The demand for high-intensity lasers has grown ever since the invention of lasers in 1960, owing to their applications in the fields of inertial confinement fusion, plasma-based relativistic particle accelerators, complex X-ray and gamma-ray sources, and laboratory astrophysics. To create such high-intensity lasers, free-running lasers were either Q-switched or mode-locked to increase the peak power to the gigawatt range. Later, chirped pulse amplification was developed, allowing the generation of peak power up to <semantics>1012</semantics> W. However, the next generation of high-intensity lasers might not be able to be driven by the solid-state technology alone as they are already operating close to their damage thresholds. In this scenario, concepts of amplification based on plasmas has the potential to revolutionize the laser industry, as plasma is already a broken-down medium, and hence does not pose any problems related to the damage thresholds. On the other hand, there are many other aspects that need to be addressed before developing technologies based on plasma-based amplification, and they are being investigated via theoretical and numerical methods and supported by several experiments. In this report, we review the prospects of employing plasma as the medium of amplification by utilising stimulated scattering techniques, such as the stimulated Raman scattering (SRS) and stimulated Brillouin scattering (SBS) techniques, to modulate high-power laser pulses, which would possibly be the key to the next generation of high-power lasers. The 1980s saw the commencement of research in this field, and possibilities of obtaining high peak powers were verified theoretically with the help of numerical calculations and simulations. The extent of amplification by these stimulated scattering schemes are limited by a number of instabilities such as forward Raman scattering (FRS), filamentation, etc., and here, magnetised plasma played an important role in counteracting these parasitic effects. The current research combines all these factors to experimentally realise a large-scale plasma-based amplifier, which can impact the high-energy laser industry in the near future.